Government Strategic Collaborative Partnership in Tourism Affairs A comparison of two Indonesian Cities - HARDINI, HEVI KURNIA (Jurnal Studi Pemerintahan, 2018)
This paper is aimed to investigate the strategic collaborative partnership in managing local tourism affairs as part of Indonesian decentralization schemes. The qualitative method is applied in order to describe the critical analysis about the existence of government strategic collaborations in Malang and Batu cities of Indonesia. The main finding is that the formal government partnership has not been established yet between the two cities. However, the strategic informal collaboration of tourism management culturally exist in both cities. In addition, Malang city government has made one step ahead by conducting feasibility study about the formal collaborative partnership in tourism affairs. There are several limitations on this study regarding the recent practice of decentralized tourism management affairs in both cities, also limited secondary data on legal documents about partnership progresses. The study recommends both local governments should utilize the cultural concept of Arek as their common cultural identity in order to make the formal government partnership possible. Hence the possible model of collaborative partnership which are Cooperative Construction and Joint Services models could be established. As a result, both policies and information could be exchanged integrally in term of tourism management affairs. The research value proposes utilizing the cultural identity of Arek, it means common identity for young people in Batu and Malang cities as the starting point towards the formal partnership establishment. Since these cities are experiencing sectoral ego in term of local government implementation, but they are solid entity in terms of AREMA (Arek Malang â€“ Malang Young People) even they use this identity to support tourism affairs collaboratively.Â Keywords: Tourism management, collaborative governance, government partnership and decentralization